Et brev fra Poul Martin Møller til Rasmus Møller - Ravn, Kim Steen (Danske Studier, 2024)
Seven years ago, The Royal Library bought an unknown letter from Poul Martin Møller to his father Bishop Rasmus Møller. The letter is dated 13 of August 1836, and is only the third known letter from 1836. Møller writes about public and private matters: the latest news from Copenhagen’s cultural life, the university and his concerns about the family’s economy and his children’s education. The letter is transcribed and provided with explanatory notes.